CAPITAL ADEQUACY RATIO, LOAN DEPOSIT RATIO DAN NON PERFORMING LOAN TERHADAP PROFITABILITAS - Alfian Agus Putranto; Farida Titik Kristanti; Dewa Mahardika (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2017)
ROA is used to measure the ability of the bank’s management in obtaining the overall profit of the total assets owned. This study aims to examine the influence of Capital Adequacy Ratio (CAR), Loan Deposit Ratio (LDR) and Non Performing Loan (NPL). Profitability is proxied by Return on Assets (ROA) in Commercial Bank listed on Indonesia Stock Exchange (BEI) in the period of 2011-2015. The population in this study are the commercial bank listed on the Stock Exchange. Sample selection technique used is purposive sampling and acquired 31 commercial banks with the 2011-2015 study period. Methods of data analysis is panel data regression analysis. The results showed that simultaneous Capital Adequacy Ratio (CAR), Loan Deposit Ratio (LDR) and Non Performing Loan (NPL) have a significant effect on profitability. While partially, Capital Adequacy Ratio (CAR) significant positive effect, Non Performing Loan (NPL) significant negative effect, while Loan Deposit Ratio (LDR) has no effect on profitability.